Optically Stimulated Luminescent Dosimetry for High Dose Rate Brachytherapy - Tien, Christopher J.; Ebeling, Robert; Hiatt, Jessica R.; Curran, Bruce; Sternick, Edward (Frontiers in Oncology, 2012)
Purpose: The objective was to determine whether optically stimulated luminescent dosimeters (OSLDs) were appropriate for in vivo measurements in high dose rate brachytherapy. In order to make this distinction, three dosimetric characteristics were tested: dose linearity, dose rate dependence, and angular dependence. The Landauer nanoDotTM OSLDs were chosen due to their popularity and their availability commercially. Methods: To test the dose linearity, each OSLD was placed at a constant location and the dwell time was varied. Next, in order to test the dose rate dependence, each OSLD was placed at different OLSD-to-source distances and the dwell time was held constant. A curved geometry was created using a circular Accuboost® applicator in order to test angular dependence. Results: The OSLD response remained linear for high doses and was independent of dose rate. For doses up to 600 cGy, the linear coefficient of determination was 0.9988 with a response of 725 counts per cGy. The angular dependence was significant only in “edge-on” scenarios. Conclusions: OSLDs are conveniently read out using commercially available readers. OSLDs can be re-read and serve as a permanent record for clinical records or be annealed using conventional fluorescent light. Lastly, OSLDs are produced commercially for $5 each. Due to these convenient features, in conjunction with the dosimetric performance, OSLDs should be considered a clinically feasible and attractive tool for in vivo HDR brachytherapy measurements.